Analysis of relationship between language applications and culture; Angkola- Mandailing community - Anna Leli Harahap (Aksara: Jurnal Bahasa dan Sastra, 2021)
ABSTRACTThis research discussed about the relationship between language application and culture; language as a means of culture in Angkola- Mandailing community, and this research intended to know the relationship between language application and culture in Angkola Angkola- Mandailing community. This research was conducted by qualitative-descriptive method that describes the relationship between language application and culture based on Nababan's theory (Nababan, 1986).  The results of this research are that the relationship between language and culture in Angkola ethnic:  1) language as a means of cultural development; for example margondang, mangayun. 2) Language as a pathway for cultural heir; for example: martahi /marpege-pege, makkobar.  3) And language as an inventory of cultural characteristics; markusip which is no longer practiced by young people in Padangsidimpuan, however, in Angkola- Mandailing community knows what that (markusip). So the relationship between language and culture is very clear in this research, because without language it is culture, and culture includes language.Keywords: Language Applications and Culture; development, heir, inventory